2013
DOI: 10.1111/cmi.12225
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 masks fibronectin-binding protein A-mediated inflammatory activation ofStaphylococcus aureusinfected monocytes

Abstract: SummaryBinding to fibronectin (FN) is a crucial pathogenic factor of Staphylococcus aureus mediated by fibronectin-binding protein A (FnBP-A) and extracellular adherence protein (Eap). Recently, we have shown that binding of soluble CD163 (sCD163) to FN linked to these molecules exhibits anti-microbial effects by enhancing phagocytosis and killing activity of S. aureus-infected monocytes. However, it remained unclear whether sCD163 also influences the monocytic activation status. Using genetically modified sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…GC-induced CD163 has been reported as an innate immune sensor for certain bacteria in human monocytes ( E. coli, S. aureus ) (124). Further studies demonstrated that soluble CD163 can directly bind to fibronectin bound to the staphylococcal surface and this enhances phagocytosis and also killing of bacteria while preventing human monocytes from overwhelming inflammatory response during staphylococcal infections (125, 126). GC-mediated induction of efferocytosis by lung macrophages in mice was also associated with increased uptake of Streptococcus pneumoniae but reduced bactericidal functions of these cells (127).…”
Section: Gcs Effects On Phagocytosismentioning
confidence: 99%
“…GC-induced CD163 has been reported as an innate immune sensor for certain bacteria in human monocytes ( E. coli, S. aureus ) (124). Further studies demonstrated that soluble CD163 can directly bind to fibronectin bound to the staphylococcal surface and this enhances phagocytosis and also killing of bacteria while preventing human monocytes from overwhelming inflammatory response during staphylococcal infections (125, 126). GC-mediated induction of efferocytosis by lung macrophages in mice was also associated with increased uptake of Streptococcus pneumoniae but reduced bactericidal functions of these cells (127).…”
Section: Gcs Effects On Phagocytosismentioning
confidence: 99%
“…sCD163 protects monocytes from hyperactivation during bacterial infections by dampening the secretion of the proinflammatory cytokines TNF-α, IL-1β, IL-6 and IL-8 (38). The actions of sCD163 and TNF-α seem to be interconnected, and the sCD163/TNF-α ratio is higher in patients with uncomplicated malaria (39).…”
Section: Scd163 Expressionmentioning
confidence: 99%
“…CD163 expression is up-regulated by glucocorticoids, IL-6, 10 and 12 and M-CSF (Macrophage colony-stimulating factor) and down-regulated by IL-4, interferon-c and TNF-α [22]. sCD163 diminishes the secretion of IL-1β and IL-6 and 8, and consequently prevents monocytes from hyperactivation [23]. Furthermore, activated M2 macrophages (which are CD163 + ) are involved in wound healing and tissue repair [24].…”
Section: Discussionmentioning
confidence: 99%